2021
DOI: 10.2981/wlb.00782
|View full text |Cite
|
Sign up to set email alerts
|

Livestock depredations by leopards in Pir Lasura National Park, Pakistan: characteristics, control and costs

Abstract: Conservation of large carnivores in protected areas with high human use or habitation is challenging due to ecological, political and socioeconomic factors. Understanding underlying patterns of human-carnivore interactions is vital for their conservation. We investigated patterns and costs of livestock depredations by common leopards Panthera pardus in and near Pir Lasura National Park, Pakistan, using standardized questionnaires to collect data from 133 respondents during 2014-2015. Respondents lost 209 anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…As for human guarding, shepherds have deterred leopards for a long time (e.g. Sidhu et al 2017, Naha et al 2020, Akrim et al 2021) and they are effective in reducing the number of attacks by carnivorans (Soofi et al 2022b). In spite of these considerations, the number of shepherds is declining globally and, therefore, incentives from governments should be considered (Soofi et al 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…As for human guarding, shepherds have deterred leopards for a long time (e.g. Sidhu et al 2017, Naha et al 2020, Akrim et al 2021) and they are effective in reducing the number of attacks by carnivorans (Soofi et al 2022b). In spite of these considerations, the number of shepherds is declining globally and, therefore, incentives from governments should be considered (Soofi et al 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…A combination of qualitative methods, specifically key informant interviews, and quantitative methods, using structured interviews with a detailed questionnaire, were employed to collect data from the field, as has been implemented in previous studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Structured interviews were conducted with 311 respondents from 40 villages with documented livestock depredation incidents and a high concentration of herding activity.…”
Section: Methods: Human-carnivore Conflict Surveymentioning
confidence: 99%
“…Livestock depredation by large mammalian predators inflicts significant economic losses on impoverished pastoral communities across Pakistan, jeopardizing village-level food security [21]. Consequently, predation on livestock remains a primary driver of human-carnivore conflict and a challenge for wildlife conservation efforts [22].…”
Section: Introductionmentioning
confidence: 99%
“…Communities near protected areas (PAs) suffer from crop-raiding and livestock predation, which is often the biggest cause of conflict in Africa [ 7 ]. People residing inside PAs are even more exposed and vulnerable to problem-causing wild animal species [ 9 , 10 ]. In Ethiopia, Tamrat et al [ 11 ] concluded that livestock predation is intense in and around a protected sanctuary.…”
Section: Introductionmentioning
confidence: 99%